2020
DOI: 10.1177/2056305120978376
|View full text |Cite
|
Sign up to set email alerts
|

Sharenting, Peer Influence, and Privacy Concerns: A Study on the Instagram-Sharing Behaviors of Parents in the United Kingdom

Abstract: Parental sharing of child-related content on social network sites, termed “sharenting,” is often the target of criticism. Yet, through sharenting, parents can find support systems, a way to stay in touch with relevant others, and even an opportunity for additional income. This study contributes to knowledge on antecedents of sharenting. It explores the impact of parents’ privacy concerns on the sharing of child-related content, as well as on their general Instagram sharing. In this study, we differentiate betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 68 publications
1
27
0
3
Order By: Relevance
“…A post hoc power analysis was conducted using GPower (Erdfelder et al, 1996). The effect size used for this assessment was 0.25 based on previous research on sharenting in the U.K. (Ranzini et al, 2020). The analysis revealed that statistical power for this study was between 0.92 and 0.94 depending on the analysis run, thus there was more than adequate power to observe a small to moderate effect size.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A post hoc power analysis was conducted using GPower (Erdfelder et al, 1996). The effect size used for this assessment was 0.25 based on previous research on sharenting in the U.K. (Ranzini et al, 2020). The analysis revealed that statistical power for this study was between 0.92 and 0.94 depending on the analysis run, thus there was more than adequate power to observe a small to moderate effect size.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Understanding the multidimensional nature of sharenting decisions is important as it could help the development of more suitable programs to encourage safer sharenting behaviors. Recent research exploring sharenting behavior of U.K. parents on Instagram reported that peer influence can be a strong predictor of sharenting (Ranzini et al, 2020). Facebook, however, is still the most widely used social media platform (YouGov, 2020).…”
mentioning
confidence: 99%
“…Specifically, sharenting can interfere with children's right to a private identity, autonomy, impression management and safety (see also Donovan, 2020). Both parents and third parties can also potentially use data about children in ways that can be revealing, embarrassing or even dangerous (Convention on the Rights of the Child, 1989;Holiday et al, 2022;Ranzini et al, 2020). This includes:…”
Section: Parents' Concerns About the Privacy Of Their Childrenmentioning
confidence: 99%
“…Ketiadaan kebijakan dan peraturan hukum yang jelas, diiringi dengan rendahnya tingkat literasi media, membuat orang tua merasa bahwa membagikan foto dan video anaknya ke media sosial adalah hal yang wajar, terlebih merasa bahwa itu hak mereka sebagai orang tua (Kumar & Schoenebeck, 2015;Steinberg, 2017). Ranzini et al (2020) membedakan dua jenis privasi yang terkait dengan sharenting. Pertama, privasi umum, yaitu privasi yang berkaitan dengan konteks sosial dan institusional.…”
Section: Sharenting Dan Privasi Anak: Studi Netnografi Pada Unggahan ...unclassified